2017
DOI: 10.1038/s41598-017-03126-9
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nitrogen and phosphorus stoichiometry of three wetland plants distributed along an elevation gradient in Dongting Lake, China

Abstract: We examined foliar nitrogen (N) and phosphorus (P) stoichiometry of 3 wetland plants (Phalaris arundinacea, Miscanthus sacchariflorus, and Carex brevicuspis) distributed along an elevation gradient in the Dongting Lake, China, and how this stoichiometry is related to soil physico-chemical characteristics, elevation, and flooding days. Plant and soil samples were collected from 3 lakeshore sites. Total N and P concentrations of plants and six physico-chemical characteristics of the soil were measured, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
(47 reference statements)
3
14
0
Order By: Relevance
“…This lake is the second largest freshwater lake in China and has the largest water exchange capacity with the Yangtze River ( Xie and Chen, 2008 ). Our previous studies confirmed that plants were limited by P in this lake ( Li et al, 2017 , 2018 ), but it has received increasing inputs of P mainly due to the use of agricultural fertilizer in the local area. The quantity of P input into the lake is about 4.1 × 10 4 t annually ( He et al, 2009 ).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…This lake is the second largest freshwater lake in China and has the largest water exchange capacity with the Yangtze River ( Xie and Chen, 2008 ). Our previous studies confirmed that plants were limited by P in this lake ( Li et al, 2017 , 2018 ), but it has received increasing inputs of P mainly due to the use of agricultural fertilizer in the local area. The quantity of P input into the lake is about 4.1 × 10 4 t annually ( He et al, 2009 ).…”
Section: Introductionsupporting
confidence: 71%
“…Another possibility is that P was not a limiting nutrient in the Sanjiang Plain Wetland ( Mao et al, 2016 ). However, our previous study showed that C. brevicuspis was limited by P at Dongting Lake ( Li et al, 2017 , 2018 ); this might explain why the addition of P promoted C. brevicuspis growth.…”
Section: Discussionmentioning
confidence: 88%
“…Sediment demand exceeds the C supply, non-structural carbohydrates will only slightly accumulate (Wang et al, 2018). Similar to RGR, plant C concentrations in both species were also higher in the clay treatment than in other sediment types, as soil nutrients are the main determinants of plant nutrient concentrations and therefore influence plant growth (Li et al, 2017b). Wang et al (2015b) and Zeng et al (2017) also reported that nutrient-rich sediment conditions result in high C concentration.…”
Section: Water Level (W)mentioning
confidence: 67%
“…The mean annual temperature is 16.8°C, with hot summers (June-August, 27.3°C) and cold winters (December-February, 5.8°C). The mean annual precipitation is 1,382 mm, with more than 60% of the rain falling from April to August (Li et al, 2017b).…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…Knowledge of the influence of soil properties on the plant communities can be utilized in restoration programs where the choice of suitable species/communities is required in revegetation. This study increases our understanding of the distribution patterns of wetland plants and the dominating environmental aspects in the basin, and could provide a theoretical basis for the design of sustainable protection and reclamation of wetland ecological environments [23]. thank Prof. Y. Natuhara at Graduate School of Environmental Studies, Nagoya University for his support.…”
Section: Discussionmentioning
confidence: 88%